A contribution to the definition of a new method to predict the catastrophic disintegration of spacecraft after collision with large orbital debris - Zaccariotto, M.; Francesconi, A.; Galvanetto, U. (Acta astronautica, 2016)
The main limitation of the currently adopted method for predicting spacecraft catastrophic fragmentation due to a collision with large debris is the total independence of the critical value of the energy-to-target mass ratio from both the satellite configuration and the impact point; in fact these two issues are not accounted for by the classical 40J/g rule. To go beyond this limitation, the method proposed in this paper evaluates the distribution of impact energy into the system using the mechanical properties of the structural parts and the knowledge of the impact location. In this way, it becomes possible to predict how impact energy is partitioned among some selected macroscopic structural parts, each of them is finally evaluated versus its own minimum value of impact energy for which the part is fragmented (shattering threshold). Energy partition is performed by solving a system of equations written according to Statistical Energy Analysis (SEA). The paper describes in detail the proposed energy-partition method and presents its application to a geometrical representative model of a spacecraft subject to impact at different points. Results are finally compared to those obtained by the application of the classical 40J/g rule. It is shown that the evaluation of spacecraft disintegration is highly influenced by the impact point and the structural properties of the components. •A new method to predict catastrophic disintegration due to impact is presented.•It uses a strategy based on statistical energy analysis.•Impact consequences depend on impact location, S/C geometry and mechanical properties.•The method requires limited computational resources.